PENGARUH PERBEDAAN RASIO WORK INTERVAL DAN REST INTERVAL TERHADAP KECEPATAN LARI - Widodo, Slamet (Pendidikan Dan Kepelatihan Olahraga, 2008)
The aim of this research is to know (1) the difference in effect between interval anaerobic training with working time ratio and the time off 1 : 5 and 1 : 10 on the achievement of 100 m sprint. (2) Interval anaerobic training its give better influence with working time ratio and the time off 1 : 5 and 1 : 10 on the achievement of 100 m sprint.The research used experiment method with macthed by subjects design. The research population is the male students of Madrasah Aliyah Al Mukmin Ngruki Sukoharjo. The variable research consist of two independent variable i.e. interval anaerobic training with the ratio of 1:5 and 1:10, and one dependent variable is 100 m sprint achievement. The technique of gathering data used test technique and measurement. The data of 100 m sprint achievement was taken by doing running test as for as 100 m. Data analysis technique is done by analysis t, on significant grade of 5%. The conclusion of the research : (1) There is a significant difference in effect between interval anaerobic training with the ratio of 1 : 10 and 1 : 5 toward the achievement of 100 m sprint. (2) Interval anaerobic training with working time ratio and the time 1 : 10 give better influence to be compared to ratio 1 : 5 the achievement of 100 m sprint.